STRATEGIC DEVELOPMENT AND CHALLENGES OF ITS POWER SUPPLY - Alexander A. Gajour (Вестник Российского экономического университета имени Г. В. Плеханова)
All countries aim at designing the program of strategic development. It is caused both by expectations of the new technological structure deployment and ambitions to retain their positions in the global labour division. The article shows the situation with making decisions concerning further strategic development in the world, in particular in China, the US and Russia. In China – it is mainly the support of state-owned enterprises, especially in zones which are important for economic security and the development of infrastructural communicative projects. In the US – it is the growth in power reserves on the basis of the vast shale project aiming at global economic expansion. Proposals of the ‘United Russia’ on strategic development of the country are provided: trebling of the middle class, equal access to infrastructure, education, Public Health. Infrastructure is the center of technological spurt, which will require decline in time and cost of transactions. Power supply of the proposed direction of strategic development was studied. The contribution of passive measures raising the level of power saving was estimated. The need in active measures, i. e. steps based on the growth in power carriers’ supply was shown. In this connection it was mentioned that power costs for providing artificial living surroundings in Russia are twice as high and even more as in Central Europe. The authors underline the necessity to introduce a common system of criteria for power efficiency for all objects of infrastructure and industry, from buildings to technological processes. They compared the cost of transactions in the European part of Russia and Western Europe, Germany. Finally, they came to the conclusion that it is essential to drop prices for all types of fuel in Russia in order to develop economy in general and to provide a growth in power resource production to guarantee strategic development.